L’antropo-etica di Edgar Morin come via per interpretare la complessità dell’esistere - Manuela Gallerani (Studi sulla Formazione, 2022)
This essay proposes a critical analysis of the role of the ethics of humankind (anthropo-ethics), a subject addressed by Edgar Morin from an original (pedagogical) point of view, in his essay The seven knowledges necessary for the education of the future (1999), a subject upon which he repetedly returns up to his 2020 essay The fraternity, why? Resisting the cruelty of the world. The teaching of different disciplines, subjects and fields of study conveyed through a perspective of complex knowledge must, by necessity, promote an anthropo-ethics approach capable of revealing and respecting the multiple characteristics of the human condition: as an individual belonging to the human species, a person, a citizen of the world and a member of a socio-historical and cultural environment. On the basis of these assumptions (and awareness) it follows, that anthropo-etics can guide the development of a more equitable and democratic culture, that is more respectful of people, the environment and the (not only ours) Earth-Homeland.